PERKEMBANGAN DIGITALISASI AL-QUR’AN: DAMPAKNYA TERHADAP PEMAHAMAN GENERASI MILENIAL - Riza Awal Novanto; Tamrin; Sawaluddin Siregar; Khasana Oriza Sativa (Yayasan Baitul Hikmah al-Zain, 2025)
The digitalization of the Qur’an is one form of Islam’s adaptation to the development of information technology. This phenomenon is marked by the emergence of various Qur’anic applications, tafsir websites, and Islamic content on social media, which facilitate access for the public especially the millennial generation in reading and understanding the Qur’an. This study aims to examine the impact of Qur’anic digitalization on how millennials comprehend the content of the Qur’an. The research uses a descriptive qualitative approach, with data collected through interviews and documentation studies involving university students who use digital Qur’anic applications. The findings show that digitalization offers ease of access to Qur’anic texts and interpretations in a fast and flexible manner. However, the understanding gained is often superficial due to the lack of guidance from tafsir scholars or religious teachers. Moreover, digital distractions also affect users' concentration in grasping the meaning of the verses. Therefore, although Qur’anic digitalization opens new opportunities for religious learning, it still requires integration between technology and contextual, in-depth religious education